2019
DOI: 10.3389/fimmu.2019.02001
|View full text |Cite|
|
Sign up to set email alerts
|

A Distinct Subset of Highly Proliferative and Lentiviral Vector (LV)-Transducible NK Cells Define a Readily Engineered Subset for Adoptive Cellular Therapy

Abstract: Genetic engineering is an important tool for redirecting the function of various types of immune cells and their use for therapeutic purpose. Although NK cells have many beneficial therapeutic features, genetic engineering of immune cells for targeted therapy focuses mostly on T cells. One of the major obstacles for NK cell immunotherapy is the lack of an efficient method for gene transfer. Lentiviral vectors have been proven to be a safe tool for genetic engineering, however lentiviral transduction is ineffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 40 publications
10
46
1
Order By: Relevance
“…NK-cell receptors expression was assessed on untouched and BaEV-LV treated NKAES, which were either transduced (GFP+) or non-transduced (GFP-) ( Figure 1E). There was no difference in CD56, CD16, NKG2D, NKG2A, NKp30, NKp44, and NKp46 receptors expression, suggesting that those markers are neither linked to the transduction efficiency, nor affected by the transduction (Figure 1E), unlike what has been recently reported (7). This difference could be attributed to the different expansion system used in our study.…”
Section: Resultscontrasting
confidence: 64%
“…NK-cell receptors expression was assessed on untouched and BaEV-LV treated NKAES, which were either transduced (GFP+) or non-transduced (GFP-) ( Figure 1E). There was no difference in CD56, CD16, NKG2D, NKG2A, NKp30, NKp44, and NKp46 receptors expression, suggesting that those markers are neither linked to the transduction efficiency, nor affected by the transduction (Figure 1E), unlike what has been recently reported (7). This difference could be attributed to the different expansion system used in our study.…”
Section: Resultscontrasting
confidence: 64%
“…Interestingly, these data suggest that the key for a high transduction rate was the pseudotyping of retroviral vectors with RD114-TR. Our findings are consistent with a recent publication by Bari et al, which showed that PB-derived NK cells were poorly transduced by lentiviral/VSV-G based transduction (57). But using a modified baboon envelope glycoprotein (BaEV) (58) to pseudotype lentiviral CD19-CAR particles, an average transduction efficiency of 70% could be reached and ASCT-2 has been proposed as the entry receptor for BaEV (59).…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, the use of BaEV pseudotyped LVs has overcome this obstacle and showed a 20-fold increase in the transduction efficiency when compared to the VSV-G pseudotyped LVs. What is more important, CAR expressing NK cells showed improvement in functionality and a higher ability to kill cancer cells [40,41]. This is proof of concept for the generation of CAR-NK cells in vitro, which may become powerful immunotherapeutic products in the future.…”
Section: Gene Therapy Using Natural Killer Cellsmentioning
confidence: 85%
“…Additionally, BaEV-LVs were able to transduce resting naïve B cells and memory B cells (20-40% efficacy) which had not been reported before [42]. In the case of T cells, recent data demonstrated that BaEV pseudotyped LVs are capable of transducing not only naïve T cells but also early thymocytes and natural killer cells with high transduction rates (up to 80%; Table 1) [39][40][41].…”
Section: Pseudotyping Of Lvs With Baboon Endogenous Virus and Feline mentioning
confidence: 91%